Business Level Strategy Analysis in Burger King Company - Teo Laiy Soon Irpan Ardiansyah; Helen Salwa; Vitty Novita; Eriva Riesquita; Esther Agustina (Universitas Muhammadiyah Makassar, 2024)
Burger King, from the name alone, you know that this company is engaged in the culinary field, which is the point of its name, namely burgers, which is definitely the main menu of the name. Currently, there are many companies or individuals selling this food, one of which is Burger King. Burger King was first established in Miami, Florida, America. Currently, Burger King has almost 19,247 branches worldwide and already has 31 branches in all cities in Indonesia. Burger King has a variety of very interesting menu variants, not only burgers but also fried chicken, potatoes, and various other menus that are no less delicious than their burgers. Burger King also makes a packaged menu which contains potatoes and drinks too, but we as consumers can also buy certain foods that we want. Burger King also often makes special menus that are issued only at certain moments or collaborates with other food brands to make it more attractive to consumers. In Indonesia, Burger King has also included its company in online applications such as gofood, grab, and others. Burger King connoisseurs are not only adults but all people, from children to the elderly, even like this food. Therefore, our goal in choosing Burger King as the company we studied was to see how influential the Business level strategy is in meeting customer needs and also increasing sales which has its own charm compared to other competing companies.